ANALISIS KORELASI DAN JALUR DALAM PENENTUAN KRITERIA SELEKSI UBI JALAR (Ipomoea batatas (L.) Lam.) BERDAYA HASIL TINGGI - Reza Prakoso Dwi Julianto; Sri Umi Lestari; Edyson Indawan (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[CORRELATION AND PATH ANALYSES FOR DETERMINING THE SELECTION CRITERIA OF HIGH YIELDING SWEET POTATO (Ipomoea batatas (L.) Lam.)]. Sweet potatoes can serve as an alternative source of healthy carbohydrates. The productivity of sweet potato is relatively low, namely 13,51 tons/ha. Plant breeding activities are one of the solutions to develop superior varieties. The success of plant breeding is determined by the success of the selection activity, one of which is determined by the selection characters used. Correlation and path analysis are used to study the closeness of the quantitative variables as the basis for a more efficient selection program. The purpose of research was to determine the character selection of sweet potato and determine the correlation pattern between the observed characters based on the correlation coefficient value along the direct and indirect effect. The research was carried out on dry land with Inceptisol dryland, at an altitude of 350 m above sea level using a randomized block design with three replications. The material used in the researh was thirteen sweet potato genotypes. The results of the correlation analysis showed that the tuber yield had a very strong and positive correlation to the number of plants (r = 0.706), tuber fresh weight (r = 0.816), and tuber BK (r = 0.898), while the tuber number variable had a moderate positive correlation. (r = 0.605). Several variables also showed a negative relationship, including stover fresh weight,% BK tuber, BK stover, and BK biomass. Based on the analysis and path analysis, the BK variable can be used as an effective and efficient selection variable in producing high yield sweet potatoes.